What daddies do best - Numeroff, Laura Joffe; Munsinger, Lynn (New York : Simon & Schuster Books for Young Readers, 2001)
Illustrations and brief text describe all the things that daddies do for their children, most importantly giving them lots of love.
Keywords: Children's stories